Efavirenz and Lopinavir/Ritonavir Alter Cell Cycle Regulation in Lung Cancer - Marima, Rahaba; Hull, Rodney; Dlamini, Zodwa; Penny, Clement (Frontiers in Oncology, 2020)
Highly active anti-retroviral treatment (HAART) is currently the most effective treatment for HIV/AIDS. Additionally, HIV positive patients receiving HAART have a better health-related quality of life (HRQoL). Cancers previously associated with HIV/AIDS also known as the AIDS defining cancers (ADCs), such as Kaposi’s sarcoma and non-Hodgkin's lymphoma have been on the decline since the introduction of HAART. However, non-AIDS defining cancers (NADCs), in particular, lung cancers have been documented to be on the rise. The association between the use of HAART components and lung carcinogenesis is poorly understood. This study aimed at elucidating the effects of two HAART components, efavirenz (EFV) and lopinavir/ritonavir (LPV/r)) on lung cancer. This was achieved through the use of in vitro cell biological approaches to assess cell health, including cell viability, Real Time Cell Analysis (RTCA) growth monitoring, evaluation of the cell cycle and progression to apoptosis, following on drug treatments. At plasma level concentrations, both EFV and LPV/r induced S-phase arrest, while at lower concentrations both drugs promoted the progression of cells into G2/M phase following cell cycle FACS analysis. At higher concentrations although cell viability assays reflected anti-proliferative effects of the drugs, this was not statistically significant. RTCA showed a significant decline in cell viability in response to the highest dose of LPV/r. Dual staining by Annexin V-FITC and PI confirmed significant pro-apoptotic effects were promoted by LPV/r. Both EFV and LPV/r exert double-edged oncogenic effects on MRC-5 and A549 lung cells, acting to either promote cell proliferation or to enhance apoptosis. This is affected by EFV and LPV/r altering cell cycle progression, with a significant S-phase arrest, this being an indication of cellular stress, cytotoxicity and DNA damage within the cell.